Developing a Trade Information Portal - World Bank (Washington, DC, 2014)
A number of countries have introduced or are considering the introduction of a trade information portal as a means of facilitating trade and increasing transparency. For World Trade Organization (WTO) members or countries in the process of acceding to the WTO, a trade information portal will assist in complying with new commitments currently being negotiated as part of the Doha Development Round. The negotiations aim to strengthen the provisions of Article X of General Agreement on Tariffs and Trade (GATT) which currently requires that all regulatory trade related information "shall be published promptly in such a manner as to enable governments and traders to become acquainted with them". In many developing nations, government agency specific websites may not exist and even when they do they are often incomplete, out of date, or the content may not cover the entire spectrum of information that a trader may wish to obtain to ensure compliance with import, export, or transit requirements. It is therefore desirable to create a single platform where all the information relating to trade from all the various agencies is aggregated under one roof and is readily available for searching and viewing. This guide discusses the issues and challenges that developing nations are likely to face when implementing a trade information portal and provides a checklist of practical guidelines for the steps that might be required in order to achieve effective implementation.